An advanced towed CTD chain for physical-biological high resolution in situ upper ocean measurements - Kock, Thomas; Baschek, Burkard; Wobbe, Florian; Heineke, Martina; Riethmueller, Rolf; Deschner, Stephan C.; Seidel, Gerd; Calil, Paulo H. R. (Frontiers in Marine Science, 2023)
Submesoscale eddies, fronts, and filaments are ubiquitous in the upper ocean and play an important role in biogeochemical and mixing processes as well as in the energy budget. To capture the high spatial variability of submesoscale processes, it is desirable to simultaneously resolve the vertical and horizontal gradients of hydrographic properties on scales of 10 m to 10 km. We present an improved towed CTD chain, for rapid quasi-synoptic in situ measurements of submesoscale oceanographic features, that is lighter, more robust and scientifically more useful than previous towed CTD chains. This new instrument provides a horizontal resolution of order of 1 m and can be towed at speeds of up to 5 m/s for measurements of the upper 120 m of the water column while providing a reasonable vertical resolution of order 1 - 10 m. Individual CTD probes are equipped with temperature, conductivity, pressure and either rapid response dissolved oxygen or fluorescence sensors at multiple depths, enabling both hydrographic and biogeochemical studies at high resolution. A flexible probe hardware allows either real-time data collection or - in a much simpler and lighter setup - internal data logging for offline post-processing. Finally, we outline the necessary post-processing steps and provide data examples.